Análisis de la proyección espacial del complejo malar en pacientes con labio y paladar hendidos - Alonso E. Cano-A; Óscar A. Botero-E; Raúl H. Cadavid-G; Aurora Gómez-J (Universidad de Antioquia, 2003)
The criteria of cephalometric evaluation used to determine the degree of compromise of the midface in patients with cleft lip and palate have depended mainly on the projection of point A with regard to the anterior cranial base, which only defines the anteroposterior growth of the maxillary bony base. The analysis of the space projection of the malar complex in patients with cleft lip and palate, is important for the diagnosis and treatment plan of the orthodontic-surgical patient. The purpose of this study is to establish by means of conventional diagnostic x-rays, the behavior of the malar region in the three planes of the space. Measures of frequency and central tendency and analysis of variance were determined for the following lineal and angular measurements: Cephalic (SNO, NOA, Or-Fr); P-A (RMS-Za right and left); Submentovertex (I measures the distance between the anterior tangent of the right and left malar with the anterior tangent of the occipital foramen, and the difference between them, the external tangent of the right and left malar with the plane RMS, and the difference between them). The study concludes that the malar complex is more retrusive in the sagittal plane, more inferior in the vertical and less expressive transversely in patients with cleft lip and palate. There were no significant differences with regard to the variable sex.